Duodenal Hematoma following Endoscopic Duodenal Biopsy: A Case Report and Review of the Literature - Daniel R Diniz-Santos; Romilda C de Andrade Cairo; Hélio Braga; Cesar Araújo-Neto; Igelmar B Paes; Luciana R Silva (Canadian Journal of Gastroenterology, 2006)
Duodenal hematoma is a rare complication of endoscopic duodenal biopsy that occurs mainly in children or adults with impaired coagulation. The clinical presentation consists of signs of intestinal obstruction, and pancreatitis and direct hyperbilirubinemia are possible complications caused by ampullary obstruction. A case of a six-year-old girl who presented with a duodenal hematoma and acute pancreatitis after having an endoscopic duodenal biopsy is reported. A review of the literature and data from all similar cases reported so far are briefly presented and discussed.